TAUHID DAN PENDIDIKAN - Rizki, Agus Muhamad (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
The purpose of this study is to explore the concept of tauhid education and its urgency in the life of Muslims. This research adopts a qualitative approach with the type of study being library research, and the data analysis techniques employed are inductive and deductive methods.The findings of this study can be summarized as follows: First, the meaning of tauhid is to affirm the oneness of Allah in all matters that are exclusive to Him. The testimony of faith, la ilaha illallah, signifies the belief and declaration that no one has the right to be worshipped and to receive acts of devotion except Allah, along with adhering to and practicing this belief. The phrase la ilaha negates the right of worship from anything other than Allah, regardless of who or what it may be, while illallah affirms that Allah alone has the exclusive right to be worshipped. The essence of the testimony of tauhid is not merely in pronouncing or memorizing it but in fulfilling the conditions required by it, without which the testimony holds no meaning for an individual. Second, the meaning of education in Islam and the connection of tauhid as the foundation and philosophy of Islamic education are explored.